Anti-adhesion polyamide film and preparation method thereof

By designing an anti-adhesion layer and a corona layer in the polyamide film, combined with the composition of polybutylene succinate resin and functional masterbatch, the problem of sticky food residues caused by the low surface tension of the polyamide film has been solved and achieved Better anti-adhesion effect and mechanical properties.

CN119329158AActive Publication Date: 2025-01-21FUJIAN CHANGSU IND CORP LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411362193.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The surface tension of polyamide films is low, resulting in viscous food residues, affecting product quality and appearance.

Method used

A polyamide film with a film layer structure consisting of an anti-adhesion layer, a core layer and a corona layer from the outside to the inside. The anti-adhesion layer is composed of polybutylene succinate resin, functional masterbatch and copolymer polyamide resin. Halo treatment adjusts surface tension.

Benefits of technology

It effectively reduces the surface adhesion of the polyamide film, prevents sticky food from adhering, improves the appearance and quality of the product, and improves the mechanical properties and barrier properties of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119329158A_ABST
    Figure CN119329158A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flexible packaging materials, and particularly relates to an anti-adhesion polyamide film and a preparation method thereof. The anti-adhesion polyamide film comprises three layers of film structures, namely an anti-adhesion layer, a core layer and a corona layer in sequence from outside to inside, wherein the anti-adhesion layer comprises the following components: 5%-8% of poly (butylene succinate) resin, 10%-15% of functional master batch and 77%-85% of copolymerized polyamide resin; the core layer comprises 100% of polyamide 6 resin, and the corona layer comprises 97%-99% of polyamide 6 resin and 3%-5% of anti-sticking master batch. According to the invention, the characteristic that poly (butylene succinate) resin can crystallize is utilized, silicon dioxide can accelerate the crystallization speed and refine the crystal grain structure in a polymer molten state, and the characteristics of poly (butylene succinate) resin and silicon dioxide are combined, so that micro-nano bulges are formed on the surface of the anti-adhesion layer, and a lotus leaf-like effect is formed; meanwhile, the synergistic amide silicone resin finally achieves the purpose of reducing the surface energy of polyamide, so that the anti-adhesion effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible packaging materials, and particularly relates to an anti-adhesion polyamide film and a preparation method thereof. Background Art

[0002] The spout stand-up bag is a fashionable new type of packaging bag, commonly used for packaging of juice, beverages, sauces and other foods. It has a high-end and novel appearance, good shelf display effect, and is easy to use. It can be used by rotating the spout cover, and the cover is closed after use for easy storage. The material of the spout bag is more environmentally friendly than that of ordinary bottles or barrels. According to data, compared with bottles of the same capacity, the raw material consumption of the spout bag can be reduced by more than 30%, the storage and transportation costs of packaging materials can be reduced by more than 60%, and the comprehensive reduction of garbage disposal can reach 5 times; it is also cleaner and more hygienic than ordinary stand-up bags.

[0003] The bag body of the spout stand-up bag is mostly made of polyamide. The reason is that polyamide can make the bag body softer and more resilient, and the polyamide layer can protect the aluminum foil layer, making it difficult to break the bag, especially for large-capacity packaging; the bottom material chooses polyamide as the middle layer to ensure the pressure resistance of the packaging bag; if the spout bag is sterilized by high-temperature cooking, it is more necessary to choose polyamide material because polyamide material is more resistant to high temperatures.

[0004] Polyamide is a polar material with good affinity. The surface tension of untreated polyamide film is low, which can easily lead to sticky food residue and affect product quality. If sticky foods such as ketchup, paste, honey and cheese adhere to the surface of polyamide packaging, it is not easy to wipe off, which not only affects the appearance of the product, but also causes quality problems such as mildew if the sauce is left on the packaging surface for a long time. Summary of the invention

[0005] In order to solve the problem that the surface tension of the polyamide film in the prior art is low and sticky food residue is easily caused, the present invention provides an anti-adhesion polyamide film and a preparation method thereof, wherein the film layer structure is an anti-adhesion layer, a core layer and a corona layer from the outside to the inside; Wherein, the components of the anti-adhesion layer include polybutylene succinate resin, functional masterbatch and copolymerized polyamide resin; The functional masterbatch comprises the following components in percentage by mass: 3% to 15% amide silicone resin, 1% to 5% silicon dioxide and 80% to 94% copolymerized polyamide resin; Among them, the mass ratio of polybutylene succinate resin to functional masterbatch is 5-8:10-15; The core layer is composed of 100% polyamide 6 resin; The components of the corona layer include 95% to 97% polyamide 6 resin and 3% to 5% anti-sticking masterbatch; The anti-sticking masterbatch includes the following components in percentage by mass: 1% to 5% of an anti-blocking agent, 1% to 5% of a lubricant and 90% to 98% of a polyamide 6 resin.

[0006] In one embodiment, the anti-adhesion layer comprises, by mass percentage, 5% to 8% polybutylene succinate resin, 10% to 15% functional masterbatch and 77% to 85% copolymerized polyamide resin.

[0007] In one embodiment, the amide silicone resin is a silicone resin modified with an amide anchoring group; Its chemical formula is: CH3(CH2) n CONH(R2SiO) m NHCO(CH2) n CH3, wherein n is 6 to 16, R is CH3, and the molecular weight is 10,000 to 100,000.

[0008] In one embodiment, the silicon dioxide has pores, and its porosity is 1.5-3.0 ml / g.

[0009] In one embodiment, the copolymerized polyamide resin is formed by copolymerizing at least two monomers of polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 1010, polyamide 1212 and polyamide MXD6.

[0010] In one embodiment, the melting point of the copolymerized polyamide is between 160°C and 190°C.

[0011] In one embodiment, the anti-blocking agent is one or more of talc, calcium carbonate, and acrylic; the lubricating agent is one or more of erucamide, oleamide, ethylene bisstearamide, polyethylene wax, and polypropylene wax.

[0012] In one embodiment, the thickness of the anti-adhesion layer is 2-5 μm; the thickness of the core layer is 10-60 μm; and the thickness of the corona layer is 1-2 μm.

[0013] The present invention also provides a method for preparing the anti-adhesion polyamide film as described above, comprising the following steps: S100, preparation of functional masterbatch: Step 1: Pour silicon dioxide into a mixing barrel equipped with a stirring device, and continuously drip amide silicone resin into multiple positions on the mixing barrel to mix thoroughly to form a powdery mixture; Step 2: Use a precise loss-in-weight scale to drop the copolyamide and the powder mixture in proportion, melt blend them through a twin-screw extruder, extrude them through a die after filtering, and then water-cooled and pelletized; S200, anti-sticking masterbatch preparation: Use a precise weight loss scale to drop polyamide 6 resin, anti-blocking agent and lubricant in proportion, melt blend through a twin-screw extruder; extrude through a die after filtering, and then water-cooled strand cutting; S300, polyamide film preparation: Step 1: The copolymerized polyamide resin and the functional masterbatch of the anti-adhesion layer, the polyamide 6 resin of the core layer, the polyamide 6 resin and the anti-adhesion masterbatch of the corona layer are respectively supplied in proportion by a feed scale, melted through their respective extruders, uniformly flowed out through a T-die, and cooled on a quenching roller to form an unstretched sheet; The temperature of the cold roller is 25-55°C; the thickness of the unstretched sheet is 150-500 μm; Step 2: After washing the small molecules of the unstretched sheet with water and plasticizing it, stretching it step by step under heating; The longitudinal stretching temperature is 45-65°C, and the stretching ratio is 2.8-3.5 times; the transverse stretching temperature is 75-85°C, and the stretching ratio is 3.0-3.5 times; Step 3, heat-setting the stretched film to obtain a polyamide film; Among them, the setting temperature is 160-220°C, and the setting time is 40-120s; Step 4: performing corona treatment on the heat-set corona layer, and then rolling and slitting to obtain an anti-adhesion polyamide film.

[0014] In one embodiment, the surface tension of the polyamide film after corona treatment is 50-54 dny.

[0015] Based on the above, compared with the prior art, the present invention has the following beneficial effects: In the anti-adhesion layer of the present invention, the polybutylene succinate resin has the property of being able to crystallize, and the silicon dioxide can transform the original homogeneous nucleation of the polymer into heterogeneous nucleation by providing the required crystal nuclei in the molten state of the polymer, thereby accelerating the crystallization rate and refining the grain structure. The silicon dioxide also has the function of adsorbing the amide silicone resin. The present invention combines the characteristics of the two to form micro-nano protrusions on the surface of the anti-adhesion layer, forming a lotus leaf effect, and at the same time synergizes with the amide silicone resin to ultimately achieve the purpose of reducing the surface energy of the polyamide, thereby achieving the anti-adhesion effect.

[0016] In a preferred embodiment, the amide silicone resin is a silicone wax powder modified with an amide anchoring group, which prevents the amide silicone resin from excessively migrating and affecting the ink printing and glue composite fastness of the corona surface.

[0017] In a preferred embodiment, the melting point of the copolymerized polyamide resin is controlled at 160-190°C, which can prevent the high-temperature processing of the polybutylene succinate resin from causing a significant decrease in the melt index, and reduce the polarity of the polyamide material to improve its compatibility with silicone.

[0018] In a preferred embodiment, the surface tension of the polyamide film is adjusted to 50-54 dny by a corona treatment method to improve its compatibility with inks, coatings or other materials.

[0019] The anti-adhesion polyamide film provided by the present invention has good mechanical properties, optical properties and barrier properties, and the anti-adhesion layer has low surface adhesion, which can solve the problem of sticky foods such as ketchup, paste, honey and cheese adhering to the packaging surface, avoiding consumer troubles and food waste.

[0020] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The positional relationships described in the drawings in the following description are based on the directions in which the components are drawn in the diagrams, unless otherwise specified.

[0022] Figure 1 A schematic structural diagram of an embodiment of the anti-adhesion polyamide film layer provided by the present invention.

[0023] Reference numerals: DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In the description of the present invention, it should be noted that all terms (including technical terms and scientific terms) used in the present invention have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and should not be understood as limitations on the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this invention.

[0026] The present invention also provides the following embodiments and comparative examples: Example 1 The weight percentage of the components of the anti-adhesion layer 100 is: 6% of polybutylene succinate, 12% of functional masterbatch, and 82% of copolymerized polyamide 6 / 12; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentage of the components of the corona layer 300 is: 4% anti-sticking masterbatch, 96% polyamide 6 resin; The mass percentage of the functional masterbatch components is: 9% amide silicone resin, 3% silica, and 88% copolymerized polyamide 6 / 12 resin; The mass percentages of the anti-sticking masterbatch components are: 3% talc, 3% ethylene bisstearamide, and 94% polyamide 6 resin.

[0027] The thickness of the anti-adhesion 100 layer is 3.3 μm.

[0028] The core layer 200 has a thickness of 20.0 μm.

[0029] The corona layer 300 has a thickness of 1.7 μm.

[0030] Example 2 The weight percentage of the components of the anti-adhesion layer 100 is: 8% polybutylene succinate, 15% functional masterbatch, and 77% copolymerized polyamide 6 / 12 resin; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentages of the components of the corona layer 300 are: 5% of anti-sticking masterbatch and 95% of polyamide 6 resin.

[0031] The mass percentage of the functional masterbatch components is: 15% amide silicone resin, 5% silica, and 80% copolymerized polyamide 6 / 12 resin; The mass percentages of the anti-sticking masterbatch components are: 5% talc, 5% ethylene bisstearamide, and 90% polyamide 6 resin.

[0032] The thickness of the anti-adhesion 100 layer is 5 μm.

[0033] The core layer 200 has a thickness of 18.3 μm.

[0034] The corona layer 300 has a thickness of 1.7 μm.

[0035] Example 3 The weight percentage of the components of the anti-adhesion layer 100 is: 5% polybutylene succinate, 10% functional masterbatch, and 85% copolymerized polyamide 6 / 12 resin; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentages of the components of the corona layer 300 are: 3% of anti-sticking masterbatch and 97% of polyamide 6 resin.

[0036] The mass percentage of the functional masterbatch components is: 3% amide silicone resin, 1% silica, and 96% copolymerized polyamide 6 / 12 resin; The mass percentages of the anti-sticking masterbatch components are: 1% talc, 1% ethylene bisstearamide, and 98% polyamide 6 resin.

[0037] The thickness of the anti-adhesion 100 layer is 2.0 μm.

[0038] The core layer 200 has a thickness of 21.3 μm.

[0039] The corona layer 300 has a thickness of 1.7 μm.

[0040] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the copolymerized polyamide 6 / 12 resin in Example 1 is replaced by copolymerized polyamide 10 / 12 resin, and the talc in the anti-sticking masterbatch component is replaced by calcium carbonate, and the rest is the same as Example 1.

[0041] The weight percentage of the components of the anti-adhesion layer 100 is: 6% of polybutylene succinate, 12% of functional masterbatch, and 82% of copolymerized polyamide 10 / 12 resin; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentages of the components of the corona layer 300 are: 4% of anti-sticking masterbatch and 96% of polyamide 6 resin.

[0042] The mass percentage of the functional masterbatch components is: 9% amide silicone resin, 3% silica, and 88% copolymerized polyamide 10 / 12 resin; The mass percentages of the anti-sticking masterbatch components are: 3% calcium carbonate, 3% ethylene bisstearamide, and 94% polyamide 6 resin.

[0043] The thickness of the anti-adhesion 100 layer is 3.3 μm.

[0044] The core layer 200 has a thickness of 20.0 μm.

[0045] The corona layer 300 has a thickness of 1.7 μm.

[0046] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that: in Comparative Example 1, no polybutylene succinate is added, the copolymerized polyamide 6 / 12 resin is replaced by polyamide 6 resin, and the ethylene bisstearamide in the anti-sticking masterbatch component is replaced by erucic acid amide, and the rest is the same as Example 1.

[0047] The weight percentage of the components of the anti-adhesion layer 100 is: 4% functional masterbatch, 96% polyamide 6 resin; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentage of the components of the corona layer 300 is: 4% anti-sticking masterbatch, 96% polyamide 6 resin; The mass percentage of the functional masterbatch components is: 9% amide silicone resin, 3% silica, and 88% copolymerized polyamide 6 / 12 resin; The mass percentage of the anti-sticking masterbatch components is: 3% talc, 3% erucamide, and 94% polyamide 6 resin.

[0048] The thickness of the anti-adhesion 100 layer is 3.3 μm.

[0049] The core layer 200 has a thickness of 20.0 μm.

[0050] The corona layer 300 has a thickness of 1.7 μm.

[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that: in Comparative Example 2, no functional masterbatch is added, the copolymerized polyamide 6 / 12 resin is replaced by polyamide 6 resin, and the rest is the same as Example 1.

[0052] The anti-adhesion layer 100 has the following components by mass percentage: 6% polybutylene succinate and 94% polyamide 6 resin; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentage of the components of the corona layer 300 is: 4% anti-sticking masterbatch, 96% polyamide 6 resin; The mass percentages of the anti-sticking masterbatch components are: 3% talc, 3% ethylene bisstearamide, and 94% polyamide 6 resin.

[0053] The thickness of the anti-adhesion 100 layer is 3.3 μm.

[0054] The core layer 200 has a thickness of 20.0 μm.

[0055] The corona layer 300 has a thickness of 1.7 μm.

[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that: in Comparative Example 3, no polybutylene succinate is added, the copolymerized polyamide 6 / 12 resin is replaced by polyamide 6 resin, the amide silicone resin in the functional masterbatch in Example 1 is replaced by methyl silicone wax, and the rest is the same as Example 1.

[0057] The weight percentage of the components of the anti-adhesion layer 100 is: 12% functional masterbatch, 88% polyamide 6 resin; The components of the core layer 200 are as follows: 100% polyamide 6 resin; The mass percentage of the components of the corona layer 300 is: 4% anti-sticking masterbatch, 96% polyamide 6 resin; The mass percentage of the functional masterbatch components is: 9% methyl silicone wax, 3% silicon dioxide, and 88% polyamide 6 resin; The mass percentages of the anti-sticking masterbatch components are: 3% talc, 3% ethylene bisstearamide, and 94% polyamide 6 resin.

[0058] The thickness of the anti-adhesion layer 100 is 3.3 μm.

[0059] The core layer 200 has a thickness of 20.0 μm.

[0060] The corona layer 300 has a thickness of 1.7 μm.

[0061] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that: No polybutylene succinate is added in Comparative Example 4, and the rest is the same as Example 1.

[0062] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that no functional masterbatch is added in Comparative Example 5, and the rest is the same as Example 1.

[0063] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that in Comparative Example 6, the copolymerized polyamide 6 / 12 resin is replaced with polyamide 6 resin, and the rest is the same as Example 1.

[0064] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that no silicon dioxide is added to the functional masterbatch component in Comparative Example 7, and the rest is the same as Example 1.

[0065] The above Examples 1 to 4 and Comparative Examples 1 to 7 were prepared by the following steps: S100, preparation of functional masterbatch: Step 1: Pour silicon dioxide into a mixing barrel equipped with a stirring device, and continuously drip amide silicone resin into multiple positions on the mixing barrel to mix thoroughly to form a powdery mixture; Step 2: Use a precise loss-in-weight scale to drop the copolyamide and powder mixture in proportion, melt blend them through a twin-screw extruder, extrude them through a die after filtering, and then water-cooled and drawn into pellets.

[0066] S200, anti-sticking masterbatch preparation: Use a precise weight loss scale to drop polyamide 6 resin, anti-blocking agent and lubricant in proportion, melt blend through a twin-screw extruder; extrude through a die after filtering, and then water-cooled strand cutting; S300, polyamide film preparation: Step 1: The copolymerized polyamide resin and the functional masterbatch of the anti-adhesion layer, the polyamide 6 resin of the core layer, the polyamide 6 resin and the anti-adhesion masterbatch of the corona layer are respectively supplied in proportion by a feed scale, melted through their respective extruders, uniformly flowed out through a T-die, and cooled on a quenching roller to form an unstretched sheet; The temperature of the cold roller is 25-55°C; the thickness of the unstretched sheet is 150-500 μm; Step 2: After washing the small molecules of the unstretched sheet with water and plasticizing it, stretching it step by step under heating; The longitudinal stretching temperature is 45-65°C, and the stretching ratio is 2.8-3.5 times; the transverse stretching temperature is 75-85°C, and the stretching ratio is 3.0-3.5 times; Step 3, heat-setting the stretched film to obtain a polyamide film; Among them, the setting temperature is 160-220°C, and the setting time is 40-120s; Step 4: performing corona treatment on the heat-set corona layer to make its surface tension 50-54 dny, and then rolling and slitting to obtain an anti-adhesion polyamide film.

[0067] Various performance tests were performed on each embodiment and comparative example, and the test standards were as follows: Thickness: GB / T20220-2006 Average thickness of plastic film and sheet samples, average thickness of rolls and unit mass area; Surface tension: Test the film surface tension according to GB / T 14216-2008; Hygroscopic elongation: The initial size of the film is L0. After being placed in a 23°C / 55% humidity environment for 48 hours, the size becomes L1. The film size unchanged rate is measured as [(L1-L0) / L0]*100%; Thermal shrinkage: GB / T12027-2004 Test method for dimensional change of plastic film and sheet upon heating; Tensile strength and elongation at break: Tested in accordance with GB / T1040.3-2006 "Determination of tensile properties of plastic films") Part 3: Test conditions for films and sheets.

[0068] The performance test results of each embodiment and comparative example are shown in Table 1.

[0069] Table 1 Performance test results

[0070] The surface tension of the adhesive surface of the polyamide film is a parameter that measures the surface free energy of the material. It determines the wettability of the material surface and thus affects the adhesion performance. High surface tension usually means high surface energy, and such a surface is more likely to adhere to other substances. On the contrary, surfaces with low surface tension have less adhesion because they have lower free energy and are less likely to interact with other substances.

[0071] It can be seen from Table 1 that the surface tension of the adhesive surface of the polyamide film prepared in Examples 1 to 4 is much lower than that in Comparative Examples 1 to 7, indicating that the anti-adhesion effect of Examples 1 to 4 is significantly higher than that of Comparative Examples 1 to 7. Although the anti-adhesion surface of the polyamide film of Comparative Example 3 has a lower surface tension, the corona attenuation of Comparative Example 3 is serious after aging, which will affect the printing and laminating effects of the film.

[0072] Hygroscopic elongation refers to the percentage of the increase in the size of a material after absorbing moisture, and it is an important parameter for measuring the dimensional stability of a material in a humid environment. The polyamide films of Examples 1 to 4 have smaller hygroscopic elongation than those of Comparative Examples 1 to 3, indicating that the polyamide films of Examples 1 to 4 have higher reliability and stability in practical applications.

[0073] Tensile strength and elongation at break are two important indicators for measuring the mechanical properties of materials. Tensile strength refers to the ability of a material to withstand the maximum stress under tensile force without breaking. Elongation at break is the ratio of the elongation of a material when it is stretched to break to its original length. The polyamide films of Examples 1 to 4 have higher tensile strength and elongation at break than those of Comparative Examples 1 to 3, indicating that the polyamide films of Examples 1 to 4 have good flexibility and extensibility, and can withstand greater mechanical forces, providing better protection for the nozzle stand-up bag.

[0074] In summary, compared with the prior art, the anti-adhesion polyamide film provided by the present invention has good moisture absorption elongation, tensile strength and elongation at break while having excellent anti-adhesion performance, and has excellent mechanical properties, which expands the application range of polyamide films and has high application value.

[0075] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present invention can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.

[0076] Although the terms such as anti-adhesion layer, core layer, corona layer, etc. are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional restrictions is contrary to the spirit of the present invention; the terms "first", "second", etc. (if any) in the description and claims of the embodiments of the present invention and the above drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An anti-adhesion polyamide film, characterized in that: The film structure is composed of anti-adhesion layer, core layer and corona layer from outside to inside. Wherein, the components of the anti-adhesion layer include polybutylene succinate resin, functional masterbatch and copolymerized polyamide resin; The functional masterbatch comprises the following components in percentage by mass: 3% to 15% amide silicone resin, 1% to 5% silicon dioxide and 80% to 94% copolymerized polyamide resin; Wherein, the mass ratio of polybutylene succinate resin to functional masterbatch is 5-8:10-15; The core layer is composed of 100% polyamide 6 resin; The components of the corona layer include 95% to 97% polyamide 6 resin and 3% to 5% anti-sticking masterbatch; The anti-sticking masterbatch includes the following components in percentage by mass: 1% to 5% of an anti-blocking agent, 1% to 5% of a lubricant and 90% to 98% of a polyamide 6 resin.

2. The anti-adhesion polyamide film according to claim 1, characterized in that: In terms of mass percentage, the anti-adhesion layer components include 5% to 8% polybutylene succinate resin, 10% to 15% functional masterbatch and 77% to 85% copolymerized polyamide resin.

3. The anti-adhesion polyamide film according to claim 1, characterized in that: The amide silicone resin is a silicone resin modified with an amide anchoring group; Its chemical formula is: CH3(CH2) n CONH(R2SiO) m NHCO(CH2) n CH3, wherein n is 6 to 16, R is CH3, and the molecular weight is 10,000 to 100,000.

4. The anti-adhesion polyamide film according to claim 1, characterized in that: The silicon dioxide has pores, and its porosity is 1.5-3.0 ml / g.

5. The anti-adhesion polyamide film according to claim 1, characterized in that: The copolymerized polyamide resin is obtained by copolymerizing at least two monomers of polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 1010, polyamide 1212 and polyamide MXD6.

6. The anti-adhesion polyamide film according to claim 1, characterized in that: The melting point of the copolymerized polyamide is between 160 and 190°C.

7. The anti-adhesion polyamide film according to claim 1, characterized in that: The opening agent is one or more of talcum powder, calcium carbonate, and acrylic; the lubricant is one or more of erucamide, oleamide, ethylene bisstearamide, polyethylene wax, and polypropylene wax.

8. The anti-adhesion polyamide film according to claim 1, characterized in that: The thickness of the anti-adhesion layer is 2-5 μm; the thickness of the core layer is 10-60 μm; and the thickness of the corona layer is 1-2 μm.

9. A method for preparing the anti-adhesion polyamide film according to any one of claims 1 to 8, characterized in that: Here are the steps: S100, preparation of functional masterbatch: Step 1: Pour silicon dioxide into a mixing barrel equipped with a stirring device, and continuously drip amide silicone resin into multiple positions on the mixing barrel to mix thoroughly to form a powdery mixture; Step 2: Use a precise loss-in-weight scale to drop the copolyamide and the powder mixture in proportion, melt blend them through a twin-screw extruder, extrude them through a die after filtering, and then water-cooled and pelletized; S200, anti-sticking masterbatch preparation: Use a precise weight loss scale to drop polyamide 6 resin, anti-blocking agent and lubricant in proportion, melt blend through a twin-screw extruder; extrude through a die after filtering, and then water-cooled strand cutting; S300, polyamide film preparation: Step 1: The copolymerized polyamide resin and the functional masterbatch of the anti-adhesion layer, the polyamide 6 resin of the core layer, the polyamide 6 resin and the anti-adhesion masterbatch of the corona layer are respectively supplied in proportion by a feed scale, melted through their respective extruders, uniformly flowed out through a T-die, and cooled on a quenching roller to form an unstretched sheet; Step 2: After washing the small molecules of the unstretched sheet with water and plasticizing it, stretching it step by step under heating; The longitudinal stretching temperature is 45-65°C, and the stretching ratio is 2.8-3.5 times; the transverse stretching temperature is 75-85°C, and the stretching ratio is 3.0-3.5 times; Step 3, heat-setting the stretched film to obtain a polyamide film; Among them, the setting temperature is 160-220°C, and the setting time is 40-120s; Step 4: corona-treating the heat-set polyamide film, and then rolling and slitting to obtain an anti-adhesive polyamide film.

10. The method for preparing the anti-adhesion polyamide film according to claim 9, characterized in that: The surface tension of the polyamide film after corona treatment is 50-54 dny.

Citation Information

Patent Citations

  • Polyamide film for flexible packaging of lithium battery and preparation process thereof

    CN110429210A

  • Ultrahigh friction masterbatch and preparation method thereof, ultrahigh friction polyamide thin film and preparation method thereof

    CN110540747A

  • Biaxially-oriented polylactic acid thin film for preventing glue reverse-sticking and preparation method therefor

    WO2024031896A1